2018
DOI: 10.1038/s41419-018-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Linc02527 promoted autophagy in Intrahepatic cholestasis of pregnancy

Abstract: LncRNA plays a crucial role in human disease. However, the expression and function of LncRNA in ICP(Intrahepatic cholestasis of pregnancy) is still not fully elucidated. In this study, we found Linc02527 was increased expression in placenta and serum of ICP patients. Ectopically expression of Linc02527 promoted autophagy and proliferate in HTR8 cells. Silencing Linc02527 suppressed the autophagy and proliferate in HTR8 cells. Mechanically study revealed that Linc02527 regulated the expression of ATG5 and ATG7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The circRNA pulldown was performed as previously described 9 . In brief, sodium dodecyl sulfate–polyacrylamide gel electrophoresis, silver staining, and MALDI-TOF-MS were performed sequentially, followed by protein identification.…”
Section: Methodsmentioning
confidence: 99%
“…The circRNA pulldown was performed as previously described 9 . In brief, sodium dodecyl sulfate–polyacrylamide gel electrophoresis, silver staining, and MALDI-TOF-MS were performed sequentially, followed by protein identification.…”
Section: Methodsmentioning
confidence: 99%
“…The specific steps of circRNA pulldown are described in our previous study [14]. Briefly, the specific proteins were identified using SDS-PAGE gel electrophoresis, silver stain and MALDI-TOF-MS [14].…”
Section: Circrna Pulldownmentioning
confidence: 99%
“…The primers were purchased from Genepharma. The 2 -ΔΔCT method was used to quantify the gene expression [14].…”
Section: Qpcrmentioning
confidence: 99%
“…Both genetic and environmental factors participate in the interpretation of the cause of ICP [ 4 ]. Several studies of ICP have revealed altered genes and proteins in many role places, including oxidative stress, cell growth, apoptosis, lipid metabolism, and immune responses [ 5 , 6 ]. Currently, the identification of ICP is verified by symptoms and the serum level of total bile acids (TBA).…”
Section: Introductionmentioning
confidence: 99%